Pengaruh Pelatihan Auditor, Tekanan Waktu, dan Skeptisisme Profesional terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan: Studi Empiris pada BPK RI Perwakilan Provinsi Sumatera Barat - Okmi Elfia; Erinos NR (Universitas Negeri Padang, 2022)
This study aims to examine the effect of auditor training, time pressure, and professional skepticism on the auditor's ability to detect fraud. Population in this study were the auditors of the BPK RI Representatives of the Province of West Sumatra, while the sample in this study was the auditors of the BPK RI Representatives of the Province of West Sumatra a total of 38 people. The sampling method used is total sampling. Sources of data in this study are primary data and data collection techniques using questionnaires. The results of this study indicate that auditor training has a positive effect on the auditor's ability to detect fraud, while time pressure and professional skepticism have no effect on the auditor's ability to detect fraud. Therefore, auditors are advised to attend training more often so that their ability to detect fraud will also improve.